Fabrication of liposomes with microfluidics-based NanoAssemblr - Chwee, Li Ying (2019)
Liposomes are spherical vesicles made up of one or more lipid bilayers that can contain an aqueous medium. A major challenge in the fabrication of liposomes is the administration of size and its distribution. This report studies the liposomes that are produced with microfluidics method using the NanoAssemblr Benchtop instrument. Precise control on size is achievable by changing the parameters (total flow rate, flow rate ratio) of the instrument. Experiments were done to fabricate liposomes at varied parameters, and better size distribution was observed at higher total flow rate and lower aqueous to organic solvent ratio. Further characterization of liposomes was done on its drug encapsulation abilities. Inclusion of cholesterol was proposed in the lipid formulation, but results showed that this did not contribute significantly to the entrapment of drug; a hydrophilic drug (Fluorescein isothiocyanate Dextran) was used. The project further explored on lipid formulation by adding PEG to organic mixture but results also showed no significant improvement in encapsulation efficiency likewise. Even though the microfluidics technology allows for better size control, future work can be done to explore other formulations that has better drug encapsulation.